Edaphic and Microclimatological Studies with Reference to Regeneration of Sal (Shorea robusta) - Samra, J. S.; Dabral, B. G.; Singh, Kalyan (Indian Forester, 1985)
Regeneration of Sal (Shorea robusta) with reference to morphological, physico-chemical, topographical and root distribution characteristics of lithosphere have been studied in West Dehra Dun Forest Division of U.P. Soil temperature and moisture at two depths along with air temperature at two heights were also monitored throughout the year. Poor drainage, deficient aeration, dispersed conditions of soil during monsoon due to high Mg, soil moisture stress coupled with hardness during dry periods and topographic location seem to be important edephic factors governing natural regeneration of Sal. Compartively low temperature and high amplitude in diurnal variation in air and soli temperature during winter season possibily due to scanty ground flora, absence of shrub layer and topographical location may be some of micro-climatic factors, affecting natural regeneration.